Application of focused ion beam to atom probe tomography specimen preparation from mechanically alloyed powders - Choi, Pyuck-Pa; Al-Kassab, Tala'at; Kwon, Young-Soon; Kim, Ji-Soon; Kirchheim, Reiner (CAMBRIDGE UNIV PRESS, 2007)
Focused ion-beam milling has been applied to prepare needle-shaped atom probe tomography specimens from mechanically alloyed powders without the use of embedding media. The lift-out technique known from transmission electron microscopy specimen preparation was modified to cut micron-sized square cross-sectional blanks out of single powder particles. A sequence of rectangular cuts and annular milling showed the highest efficiency for sharpening the blanks to tips. First atom probe results on a Fe95Cu5 powder mechanically alloyed in a high-energy planetary ball mill for 20 h have been obtained. Concentration profiles taken from this powder sample showed that the Cu distribution is inhomogeneous on a nanoscale and that the mechanical alloying process has not been completed yet. In addition, small clusters of oxygen, stemming from the ball milling process, have been detected. Annular milling with 30 keV Ga ions and beam currents >= 50 pA was found to cause the formation of an amorphous surface layer, whereas no structural changes could be observed for beam currents <= 10 pA.
Keywords: LIFT-OUT; MICROSCOPY; TEM